Reinventing or rediscovering international law? The Russian Constitutional Court’s uneasy dialogue with the European Court of Human Rights - Aksenova, Marina; Marchuk, Iryna (Oxford University Press, 2019)
This article discusses interactions between the Constitutional Court of the Russian Federation and the European Court of Human Rights. More specifically, it critically examines evolving legal reasoning of the CC with respect to its interpretation of international law. Furthermore, it reflects on broader implications of the CC’s recent rulings that reaffirm the primacy of the Constitution of the Russian Federation over the ECtHR judgments in part where they appear to be contrary to the constitutional law provisions. These rulings are anticipated to have a long-lasting effect on the Russian legal system. They reflect a changing relationship between international and domestic law and signal a shift in Russia toward a more autonomous understanding of international law rooted in the principle of sovereignty that differs from the Western narrative of the discipline. Even more broadly, these emerging new interpretations support the idea of fragmentation of international law not only from a strictly legal perspective—as a plethora of conflicting sources of law—but also from a socio-legal perspective as a discipline harboring conflicting narratives.
Keywords: 59 Ciencia Política::5901 Relaciones internacionales ::5901.03 Política internacional; ODS 5 - Igualdad de género; ODS 16 - Paz, justicia e instituciones sólidas